2019
DOI: 10.1177/0305735619878497
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of music stimuli to support mindfulness meditation

Abstract: The purpose of this study was to compare the effectiveness of and preference for different auditory stimuli in supporting mindfulness meditation. Undergraduate non-musicians ( N = 57) listened to four different auditory stimuli guiding them in a mindfulness meditation: script only (i.e., Script), steady beat (i.e., Beat), beat and harmonic progression (i.e., Harmony), and beat, harmony, and melody (i.e., Melody). This study used a within-subjects repeated-measures design with the four conditions counterbalance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 35 publications
(62 reference statements)
1
57
0
Order By: Relevance
“…Given the differences in cognitive and neural responses to music among musicians and nonmusicians, it stands to reason that a mindfulness meditation with music would have dissimilar results among these groups. A previous study by Dvorak and Hernandez-Ruiz (2019) investigated the effectiveness, preference, and usefulness of music stimuli of increasing complexity on mindfulness practice in non-musicians. Participants listened to four conditions: recorded voice of instructions for mindfulness meditation (i.e., Script condition); the Script with a bass sound played on a steady beat (i.e., Beat condition); the Script with Beat and harmonic accompaniment played by sampled strings (i.e., Harmony condition); and the Script, Beat, Harmony, and melody played by a sampled viola (i.e., Melody condition).…”
Section: Previous Findings In Mindfulness and Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the differences in cognitive and neural responses to music among musicians and nonmusicians, it stands to reason that a mindfulness meditation with music would have dissimilar results among these groups. A previous study by Dvorak and Hernandez-Ruiz (2019) investigated the effectiveness, preference, and usefulness of music stimuli of increasing complexity on mindfulness practice in non-musicians. Participants listened to four conditions: recorded voice of instructions for mindfulness meditation (i.e., Script condition); the Script with a bass sound played on a steady beat (i.e., Beat condition); the Script with Beat and harmonic accompaniment played by sampled strings (i.e., Harmony condition); and the Script, Beat, Harmony, and melody played by a sampled viola (i.e., Melody condition).…”
Section: Previous Findings In Mindfulness and Musicmentioning
confidence: 99%
“…The ability and willingness to be "drawn in deeply [by a musical stimulus]" is a trait that could explain dissimilar findings in music perception and music intervention research (Sandstrom & Russo, 2013). In Dvorak and Hernandez-Ruiz (2019), researchers found that absorption in music seemed to mediate participants' responses to the musical stimuli.…”
Section: Previous Findings In Mindfulness and Musicmentioning
confidence: 99%
“…Teams of students crafted novel music stimuli based on the compositional principles of the stimuli used in previous studies. The compositional principles of the original stimulus were decided within parameters found in the music psychology literature (Dvorak & Hernandez-Ruiz, 2019). These principles are included in the assignment description in Appendix A.…”
Section: Compositionmentioning
confidence: 99%
“…The resulting scaffolded project embedded in this CURE involved music students composing novel music stimuli for mindfulness meditation, following similar research-9 based compositional principles to the original stimuli used in previous studies (Dvorak & Hernandez-Ruiz, 2019;Hernandez-Ruiz & Dvorak, in press;. Students chose from a range of provided structures, approaches, pathways, or sources to craft the music stimuli (Willison et al, 2015).…”
Section: Scaffolded Researchmentioning
confidence: 99%
See 1 more Smart Citation